2017
DOI: 10.3727/096504017x14874323871217
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MicroRNA-216a Suppresses Proliferation, Migration, and Invasion of Glioma Cells by Targeting Leucine-Rich Repeat-Containing G Protein-Coupled Receptor 5

Abstract: Increasing studies have suggested that microRNAs (miRNAs) are involved in the development of gliomas. MicroRNA-216a has been reported to be a tumor-associated miRNA in many types of cancer, either as an oncogene or as a tumor suppressor. However, little is known about the function of miR-216a in gliomas. The present study was designed to explore the potential role of miR-216a in gliomas. We found that miR-216a was significantly decreased in glioma tissues and cell lines. Overexpression of miR-216a significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…To test the hypothesis whether modification of beta cell miRNA profile could promote their proliferation, we chose miR-216a, which has been shown to relate to cell proliferation by a number of investigators [37][38][39][42][43][44] . The PCR and ISH data confirmed the miRNA microarray findings that the expression of miR-216a in pancreatic islets increased during the development of T1D, which could be a compensatory mechanism used by the damaged beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…To test the hypothesis whether modification of beta cell miRNA profile could promote their proliferation, we chose miR-216a, which has been shown to relate to cell proliferation by a number of investigators [37][38][39][42][43][44] . The PCR and ISH data confirmed the miRNA microarray findings that the expression of miR-216a in pancreatic islets increased during the development of T1D, which could be a compensatory mechanism used by the damaged beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing studies have suggested that glioma‐associated miRNAs function as tumor suppressors by interfering with Wnt/β‐catenin. For instance, miRNA‐216a impedes glioma cell proliferation, migration, and invasion, and these events are closely linked with the suppression of Wnt/β‐catenin signaling (J. Zhang, Xu, et al, ). Both miR‐202 and miR‐139‐5p attenuate the malignant phenotypes of glioma cell by the inhibitory effect of Wnt/β‐catenin pathway, as mentioned earlier (Q. Wang, Xu, et al, ; J. Yang, Fan, Zhao, & Fang, ).…”
Section: Multiple Roles Of Mirna Regulatory Wnt/β‐catenin Signaling Imentioning
confidence: 99%
“…Consistently, miR-96/HBP1/ Wnt/β-catenin regulatory circuitry promotes the proliferation of glioma cells(Yan et al, 2014).However, increasing studies have suggested that glioma-associated miRNAs function as tumor suppressors by interfering with Wnt/β-catenin. For instance, miRNA-216a impedes glioma cell proliferation, migration, and invasion, and these events are closely linked with the suppression of Wnt/β-catenin signaling (J Zhang, Xu, et al, 2017)…”
mentioning
confidence: 99%
“…Aberrant miRNA expression is strongly correlated with the development of metastasis in various cancers, including GC [ 9 ]. miR-216a has recently been reported to play a tumor suppressive role in human cancer including glioma [ 10 ], colorectal cancer (CRC)[ 11 ] and pancreatic cancer [ 12 , 13 ]. miR-216a suppresses invasion, migration and proliferation of glioma cells by inhibiting leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5)[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-216a has recently been reported to play a tumor suppressive role in human cancer including glioma [ 10 ], colorectal cancer (CRC)[ 11 ] and pancreatic cancer [ 12 , 13 ]. miR-216a suppresses invasion, migration and proliferation of glioma cells by inhibiting leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5)[ 10 ]. Furthermore, miR-216a prohibits invasion and migration of CRC cells in vitro , and restrains liver metastasis in vivo by targeting KIAA1199 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%